Interlaboratory comparison of [delta]13C and [delta]D measurements of atmospheric CH4 for combined use of data sets from different laboratories - Umezawa, Taku; Veidt, Cordelia; Levin, Ingeborg (Atmospheric measurement techniques, 2018)
We report results from a worldwide interlaboratory comparison of samples among laboratories that measure (or measured) stable carbon and hydrogen isotope ratios of atmospheric CH4 (δ¹³C-CH4 and δD-CH4). The offsets among the laboratories are larger than the measurement reproducibility of individual laboratories. To disentangle plausible measurement offsets, we evaluated and critically assessed a large number of intercomparison results, some of which have been documented previously in the literature. The results indicate significant offsets of δ¹³C-CH4 and δD-CH4 measurements among data sets reported from different laboratories; the differences among laboratories at modern atmospheric CH4 level spread over ranges of 0.5 ‰ for δ¹³C-CH4 and 13 ‰ for δD-CH4. The intercomparison results summarized in this study may be of help in future attempts to harmonize δ¹³C-CH4 and δD-CH4 data sets from different laboratories in order to jointly incorporate them into modelling studies. However, establishing a merged data set, which includes δ¹³C-CH4 and δD-CH4 data from multiple laboratories with desirable compatibility, is still challenging due to differences among laboratories in instrument settings, correction methods, traceability to reference materials and long-term data management. Further efforts are needed to identify causes of the interlaboratory measurement offsets and to decrease those to move towards the best use of available δ¹³C-CH4 and δD-CH4 data sets.
Gesehen am 20.02.2020
Im Titel ist "delta" jeweils als griechisches Symbol dargestellt
Im Titel ist die Zahl "13" hochgestellt und die Zahl "4" tiefgestellt